To rearrange the formula \( S = \frac{1}{2}lp + B \) for the quantity of interest \( p \), we will isolate \( p \) on one side of the equation.
Here are the steps for rearranging the formula:
-
Start with the original formula: \[ S = \frac{1}{2}lp + B \]
-
Subtract \( B \) from both sides: \[ S - B = \frac{1}{2}lp \]
-
Multiply both sides by \( 2 \) to eliminate the fraction: \[ 2(S - B) = lp \]
-
Finally, divide both sides by \( l \): \[ p = \frac{2(S - B)}{l} \]
The correct rearrangement of the formula for \( p \) is: \[ p = \frac{2(S - B)}{l} \]
So, the correct answer is: \( p = \frac{2(S - B)}{l} \)